2006
DOI: 10.1093/hmg/ddl147
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of the TCF1 gene encoding hepatocyte nuclear factor-1 alpha show differential expression in the pancreas and define the relationship between mutation position and clinical phenotype in monogenic diabetes

Abstract: The generation of multiple transcripts by mRNA processing has the potential to moderate differences in gene expression both between tissues and at different stages of development. Where gene function is compromised by mutation, the presence of multiple isoforms may influence the resulting phenotype. Heterozygous mutations in the transcription factor hepatocyte nuclear factor-1 alpha (HNF1A or TCF1 gene) result in early-onset diabetes as a result of pancreatic beta-cell dysfunction. We investigated the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 42 publications
7
117
3
6
Order By: Relevance
“…In one study lower age of diabetes diagnosis has been shown to be associated with missense mutations in exons expressed in all three isomers HNF1A(A), (B) and (C) [15]. In another study, lower age of diabetes diagnosis was associated with missense mutations within the dimerisation and DNA-binding domains [16].…”
Section: Methodsmentioning
confidence: 97%
“…In one study lower age of diabetes diagnosis has been shown to be associated with missense mutations in exons expressed in all three isomers HNF1A(A), (B) and (C) [15]. In another study, lower age of diabetes diagnosis was associated with missense mutations within the dimerisation and DNA-binding domains [16].…”
Section: Methodsmentioning
confidence: 97%
“…Mutations affecting different isoforms have been associated with age at disease onset in certain studies; thus, isoforms may influence the phenotype of disease differently (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients with HNF1A truncating mutations are diagnosed at a median age of 20 years independently of the location of the mutation within HNF1A. 7,8 A similar correlation was observed with HNF4A mutations. 9…”
Section: Mutational Spectrummentioning
confidence: 75%